Disaster risk reduction and climate policy implementation challenges in Canada and Australia. (21st April 2022) - Raikes, Jonathan; Smith, Timothy F.; Baldwin, Claudia; Henstra, Daniel
ABSTRACT: Disaster risk reduction is central to managing the risks of climate change at global, national, and sub-national levels. The operationalization of disaster risk reduction, however, has been met with challenges that have restricted successful policy implementation. Drawing from document analyses and Delphi studies with government practitioners, this article examines the policy context for disaster risk reduction in Canada and Australia and investigates the state of flood and drought planning and preparedness. Results are organized around two central themes: risk (ownership and sensitivity) and engagement (stakeholder involvement and capacity-building). The findings show that public policies on disaster risk reduction in Canada and Australia reflect international discourse that advocates for a whole-of-society, risk-sensitive, and risk-informed approach. However, implementing this approach in household planning and preparedness, cross-sector planning and policy integration, terminology, and socio-cultural representation, has been hampered by several factors. Government practitioners in both countries argued that while disaster risk reduction and climate risk management continue to evolve in multi-level governance, policy implementation is constrained by the legacies of past governance arrangements that have enabled disaster risk creation and accumulation. The results presented herein suggest a need for institutional reform that better reflects the holistic and systemic relationships between disaster risk, climate change, and other policy problems. We argue that disaster risk reduction and climate risk management policies require bridging governance arrangements between these and related policy domains to foster effective multi-level implementation. Key policy insights Implementing disaster risk reduction has been inconsistent, exacerbating exposure to climate change and increasing socio-economic vulnerabilities to disaster impacts. Managing climate and disaster risk requires a holistic approach that targets vulnerable groups, tackles underlying drivers of risk, and builds capacities to support disaster risk reduction. Although disaster risk reduction and climate risk management policies continue to evolve, implementation is hindered by legacy governance arrangements that favour economic growth over sustainable, climate-sensitive disaster risk management. Transformation through the integration of disaster risk reduction and human development offers potential pathways to reduce vulnerabilities via a holistic disaster risk and climate policy approach.